Can Traditional Healing Systems Integrate With Music Therapy - Sumathy Sundar interviews T. V. Sairam - Sundar, Sumathy (Voices: A World Forum for Music Therapy, 2005)
In recent trends of attributing any kind of illness to a Bio- Psycho- Social model, the psyche and physiology are interrelated in the context of psycho- social pressures resulting in patho-physiological outcomes. Within this context, an integrated treatment approach has been welcomed by health professionals in a variety of clinical settings. This has led to the introduction of Complementary Therapies which take care of the often unmet psychological and social needs of the patients. In a country like India, known for its rich cultural heritage and traditions, many traditional healing systems like Yoga and Ayurveda have been welcomed globally and have been given scientific endorsements for their therapeutic values. One such approach called nada yoga refers to the study of the powerful influence that nada exerts on one's mind or consciousness. Dr. T V Sairam has been extensively working on nada yoga for quite some time. This interview is an attempt to answer the question if traditional healing systems like nada yoga can integrate with Music Therapy. We hope that this will be of interest to many present-day music therapists. Note that all Sanskrist terms (in italics) used in the interview are described in more detail in the Glossary at the end of the interview.